EFEKTIVITAS KONSELING KELOMPOK DENGAN TEKNIK PENGKONDISIAN AVERSI DALAM MENGATASI PERILAKU ADIKSI - Armey Rolizky; Bela Janare Putra; Suryati Suryati (Social Science and Contemporary Issues Journal, 2023)
One technique in counseling is aversion conditioning, which is used to change emotional responses to harmful or undesirable behavior in behavior therapy. This research uses a one group pre-test post-test design. A pretest was carried out on a group of research subjects, then treatment was given, and followed by a posttest using the same measurements. The method used in the research was observation, documentation and distribution of questionnaires to clients at the Palembang Ar-Rahman Drug Rehabilitation Center Foundation. The calculation results from the pre-test before the treatment was given were 60.53 and after the treatment was given and the post-test was carried out the results were 124.53. So it can be concluded that there has been an increase in the level of self-control of former drug addicts. The conclusion of this research is that before being given group counseling using aversion techniques, clients at the Ar-Rahman Palembang rehabilitation foundation lacked self-control in overcoming addictive behavior. There was an increase in overcoming addictive behavior after being given group counseling with aversion techniques to clients at the Ar-Rahman Palembang rehabilitation foundation. There is a difference in the effectiveness of group counseling and aversion techniques in overcoming addictive behavior. Keywords: Addiction, Group Counseling, Aversion Conditioning Techniques